Antigen physiochemical properties allosterically effect the IgG Fc-region and Fc neonatal receptor affinity - Yue Sun; Alberto Estevez; Tilman Schlothauer; Aaron T. Wecksler (Taylor & Francis Group, 2020)
The neonatal Fc receptor (FcRn) is a key membrane protein that plays an integral role in serum immunoglobulin (IgG) recycling, which extends the half-life of antibody. In addition, FcRn is known to traffic antigen-bound immunoglobulins (Ag-IgGs), and to interact with immune complexes to facilitate the antigen cross-presentation of peptides derived from the immune complexes in antigen-presenting cells (APCs). Studies on the IgG-FcRn molecular interactions have primarily focused on the Fc region, and only recently have shown the potential impact of the antigen-binding fragment physiochemical properties on FcRn binding. However, the effect of the antigen physiochemical properties on IgG structure as it relates to Ag-IgG-FcRn binding is not well understood. Here we used an IgG-peptide antigen complex as a model system to investigate the structural effects of the antigen's physiochemical properties on the IgG structure, and the subsequent effects of Ag-IgG-FcRn interactions. We used hydroxyl radical footprinting-mass spectrometry to investigate the structural impact on an IgG upon antigen binding, and observed that the physicochemical properties of the antigen differentially induce conformational changes in the IgG FcRn binding region. The extent of these structural changes directly correlates to the magnitude of the affinity differences between the Ag-IgG complexes and FcRn. Moreover, the antigen's physicochemical properties differentially induce structural differences within the Ag-IgG-FcRn ternary complex. We also provide electron microscopy data that shows corroborating Fab-FcRn interactions, and confirms the hypothesis of potential 2:1 FcRn:IgG binding stoichiometry. These data demonstrate antigen-induced Fc structural rearrangements affect both the affinity toward FcRn and the trimeric antigen-IgG-FcRn complex, providing novel molecular insights in the first steps toward understanding interactions of FcRn-containing large(r)-sized immune complex.